The Long-Term Impact of Parental Migration on the Health of Young Left-behind Children - Jinkai Li; Erga Luo; Bart Cockx (Institute of Labor Economics (IZA), 2023)
In 2015, 15% of all children in China were left behind in the countryside because at least one of their parents migrated to a city. We implement an event study analysis between 2010 and 2018 on five waves of the China Family Panel Studies (CFPS) to investigate the dynamic effects of parental migration on the health of left behind young children (LBC). While we find a gradual increase in medical expenditures, we do not detect any significant impact on the incidence of sickness. Furthermore, the analysis shows that the incidence of overweight declines gradually since their parents' first migration and reports suggestive evidence for mental health improvement. We argue that these long-term positive effects on health and health consumption can be explained by the transitory nature of migration, the high-quality substitution of the caregiver role by grandparents, and by a reorientation in family expenditures, partly induced by government policy.
Keywords: I15; J10; J61; 330; young left-behind children; parental migration; Hukou system; long-term impact on health; event study analysis; mechanisms analysis